Alternative Strategies for Microbial Remediation of Pollutants via Synthetic Biology - Jaiswal, Shweta; Shukla, Pratyoosh (Frontiers in Microbiology, 2020)
Continuous contamination of the environment with xenobiotics and related recalcitrant compounds has emerged a serious threat of pollution. Bioremediation is the key to eliminate persistent contaminants from the environment. The traditional bioremediation processes showed limitations, therefore, it is necessary to discover new bioremediation technologies for best results. Here, in this review, we have provided an outlook on alternative strategies for bioremediation via synthetic biology, including exploring the prerequisites for analysis of research data for developing synthetic biological models of microbial bioremediation. Moreover, cell coordination in synthetic microbial community, cell signaling, and quorum sensing are engineered for enhanced bioremediation strategies are also described along with promising gene editing tools for obtaining the host with target gene sequences responsible for the degradation of recalcitrant compounds. The synthetic genetic circuit and two-component regulatory system (TCRS) based microbial biosensors for detection and bioremediation are also briefly explained. These developments are expected to increase the efficiency of bioremediation strategies for the best results.